Participants' experiences of music, mindful music, and audiobook listening interventions for people recovering from stroke. Issue 1 (4th May 2018) - Baylan, Satu; McGinlay, Meigan; MacDonald, Maxine; Easto, Jake; Cullen, Breda; Haig, Caroline; Mercer, Stewart W.; Murray, Heather; Quinn, Terence J.; Stott, David; Broomfield, Niall M.; Stiles, Ciara; et al.
Abstract: Existing research evidence suggests that both music listening and mindfulness interventions may have beneficial effects on mood and cognition poststroke. This mixed‐methods study, nested within a pilot randomized controlled trial investigating the feasibility and acceptability of combining music listening and brief mindfulness training poststroke, explored study participants' experiences of engaging in the interventions. Fifty‐six stroke survivors who were randomized to receive an 8‐week intervention of mindful music listening ( n = 15), music listening ( n = 21), or audiobook listening ( n = 20, control) using self‐selected material participated in a postintervention individual semistructured interview with a researcher not involved in their intervention delivery. Interview questions focused on affective, cognitive, and physical experiences. Data were coded and analyzed using thematic analysis. Across groups, listening was associated with positive distraction from thoughts and worries. Mindful music listening was most strongly associated with relaxation and concentration, improved attentional control, and emotion regulation, as well as enjoyment. Music listening was most strongly associated with increased activity, memory reminiscence, and improved mood. In addition, participants provided valuable feedback on intervention feasibility and acceptability. The findings suggest that the interventions were feasible and enjoyable for people recovering from stroke.